An audit of hepatobiliary diseases in a tertiary level intensive care unit in Nepal - Shrestha, Pramesh Sunder; Acharya, Subhash Prasad; Shrestha, Gentle Sunder; Aryal, Diptesh; Udaya, Rejin Kumar; Marhatta, Moda Nath (Journal of Society of Anesthesiologists of Nepal, 2017)
Background: Hepatobiliary diseases account for significant proportion of admission in our intensive care unit, a semi-closed, 11 bedded mixed medical-surgical unit. This study was conducted to study the profile of patients with various hepatobiliary diseases who required intensive care unit admissions with the aim of identifying the need for a hepatobiliary critical care facility. Methods: A retrospective study was designed and all consecutive patients admitted with hepatobiliary problems from January 2013 till December 2013 were enrolled in the study. Results: Out of 467 patients admitted, there were 61 (13.06%) patients with hepatobiliary diseases. Out of 61 patients, there were 24 (39.3%) patients with medical cause for hepatobiliary disease and 37 (60.7%) patients with a surgical cause. The majority of the patients 52.45% were male. The overall mortality in these patients was 37.70%. The mortality in patients with surgical cause for the hepatobiliary disease was less (27.02%). Encephalopathy was a common condition leading to ICU admission. The common medical conditions were Cirrhosis secondary to Alcoholic Liver disease and Acute Fulminant Hepatic Failure. The commonest surgical conditions were Severe Pancreatitis, Post-Whipple's surgery, postoperative sepsis after Cholecystectomy, Liver Injury secondary to Road Traffic Accidents and Severe Cholangitis. Conclusion: The number of patients presenting to our multidisciplinary unit with hepatobiliary diseases is high and this group of patients have a high mortality. Though the numbers do not suggest an immediate need for a Hepatobiliary intensive care unit, the increasing trend suggests such a facility would be the need of time in near future.